ANALISIS RELEVANSI CITY BRANDING “BEAUTIFUL MALANG” MELALUI PENDEKATAN CITY BRAND INDEX DAN CITY BRAND PERSONALITY - Muhammad Mufli; Andriani Kusumawati (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
The research investigated relevance of city branding of Beautiful Malang through city brand index and city brand personality approach. City brand index describes the competitive advantages of Malang which are reviewed from six aspects that are presence, potential, place, people, pulse and prerequisite. City brand personality identification of personal characteristics of Malang City which are viewed from the five dimensions that are sincerity, excitement, competence, sophistication, and ruggnedness. The city brand index that, place get the high score. Brand personality of Malang City represent five dimension of city brand personality. The City brand index aspects of Malang City that relevant to city branding “Beautiful Malang” are place, people, pulse and potential, while indirect relevant that are prerequisites and presence. The city brand personality scale of Malang City also shows that there are a few items the brand personality of Malang City has direct relevance to the